THE ROLE OF FEEDBACK IN LANGUAGE LEARNING - Abduraximov Murodbek Baxtiyor o'g'li; Xo'shboqov Sarvar Bahrom o'g'li; Husanov Abdurahmon Juma oʻgʻli; Primov Husan Abdurasul oʻgʻli (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Corrective Feedback (CF) is a cornerstone of instructed second language acquisition (ISLA), serving as a primary mechanism for bridging the gap between a learner’s interlanguage and the target language. This article examines the efficacy of various CF strategies—specifically distinguishing between implicit and explicit interventions and their timing. By synthesizing findings from decades of empirical research, this study argues that while CF is universally beneficial compared to its absence, its effectiveness is highly contingent upon the learner’s cognitive readiness, the linguistic complexity of the target structure, and the instructional context. The paper concludes with a framework for "optimal feedback," advocating for a balanced, learner-centric approach.